KONSTRUKSI IDENTITAS TIONGHOA MUSLIM DI MAKASSAR - Kunu, Arifuddin (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2018)
This study describes how Chinese Muslims construct their identity through interaction, both with fellow Chinese non-Muslims and non-Chinese Muslims. Using Critical Discourse Analysis with the subjects are four informants from Muslim Chinese community, the results show that the construction of identity built by Chinese Muslims through good interaction with fellow non-Muslim Chinese and non-Chinese Muslims was relational. How Chinese Muslims identify themselves, will be influenced by the "Self"-"Other" faced. In negotiating their identity, Chinese Muslims apply the layered form of acculturation, which can be found in Chinese New Year celebrations. In the first layer, Islam is acculturated with Chineseness. The second tier, Islam that has been acculturated is re-acccultured with values ​​that exist in the local community. To cite this article (7th APA style): Kunu, A. (2018). Konstruksi Identitas Tionghoa Muslim di Makassar [Identity Construction of Chinese Muslim in Makassar]. Journal Communication Spectrum, 8(2), 133-146. http://dx.doi.org/10.36782/jcs.v8i2.1851